2008
DOI: 10.1542/peds.2006-3778
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Children With Heart Disease as Perceived by Children and Parents

Abstract: Overall, children with cardiovascular disease perceived lower quality of life than healthy children across all age groups. As perceived by parents, overall quality of life was not significantly different in young children with cardiovascular disease, but children with more severe cardiovascular disease have worse physical and psychosocial quality of life. One in 5 children with cardiovascular disease perceives impaired psychosocial functioning, including children with mild disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
369
10
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 284 publications
(418 citation statements)
references
References 29 publications
29
369
10
10
Order By: Relevance
“…40 In contrast, in a study using PedsQL, for both 5-to 7-year-olds and 8-to 12-year-olds, QoL in children with CHD was found to be significantly lower in all domains compared with the age-matched reference group. 33 Self-reported QoL in 8-to 12-year olds in another similar study was comparable with control subjects. 34 Younger children (aged 8-10 years) with orofacial clefts had a significantly higher average global health-oral score than the 15-to 18-year-olds.…”
Section: Studies Of Self-reported Qolmentioning
confidence: 66%
See 4 more Smart Citations
“…40 In contrast, in a study using PedsQL, for both 5-to 7-year-olds and 8-to 12-year-olds, QoL in children with CHD was found to be significantly lower in all domains compared with the age-matched reference group. 33 Self-reported QoL in 8-to 12-year olds in another similar study was comparable with control subjects. 34 Younger children (aged 8-10 years) with orofacial clefts had a significantly higher average global health-oral score than the 15-to 18-year-olds.…”
Section: Studies Of Self-reported Qolmentioning
confidence: 66%
“…Nevertheless, some studies found that parents overestimated the QoL of their children; for example, for positive emotions in children with congenital hypothyroidism 58 or for all domains for 5-to 7-year-olds with CHD. 33 Interestingly, using the same QoL instrument (KINDL), 8-to 12-year-old children with hearing impairment rated their overall QoL significantly lower than their parents did in one study, 55 whereas in another study, hearing-impaired younger children (aged 4-7 years) reported significantly better QoL than parents did on the overall score. 54 Overall, studies using either a more functioning-oriented instrument (eg, CHQ, PedsQL, TACQOL) or a more well-being-oriented instrument (eg, KIDSCREEN, KINDL) found discrepancies between self-reports and proxy reports.…”
Section: Studies Comparing Self-reports and Proxy Reportsmentioning
confidence: 91%
See 3 more Smart Citations